The Effect of Tax Planning, Profitability, Tunnelling Incentive and Capital Intensity Towards Transfer Pricing Indication - Nausika, Chilma Layla; Simbolon, Ika Pratiwi; Reyes, Mila (Universitas Pamulang, 2022)
This investigation aims to examine transfer pricing signals that may be impacted by tax strategizing, profitability, tunneling motivations, and capital intensity. The study utilized a sample of 25 mining firms listed in Indonesia between 2015 and 2019. This study employed a quantitative methodology utilizing panel data and multiple linear regression models. The present study has determined that transfer pricing is not influenced by tax planning, profitability, and capital intensity, while tunneling incentives significantly impact transfer pricing.